2015
DOI: 10.1115/1.4028993
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Dependent J-R Curves of a Dissimilar Metal Welded Joint for Connecting Pipe-Nozzle of Nuclear Pressure Vessel

Abstract: In this paper, the J-R curves of two cracks (A508 HAZ crack 2 and A508/Alloy52Mb interface crack 3) located at the weakest region in an Alloy52M dissimilar metal welded joint (DMWJ) for connecting pipe-nozzle of nuclear pressure vessel have been measured by using single edge-notched bend (SENB) specimens with different crack depths a/W (different constraint). Based on the modified T-stress constraint parameter τ*, the equations of constraint-dependent J-R curves for the crack 2 and crack 3 were obtained. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results showed that the proposed equation resulting from the parametric analysis could be employed to predict the static burst pressure of cylindrical shell intersections for a wide range of geometric ratios. Wang et al [211] obtained the equations of constraint-dependent J-R curves for the cracks of a dissimilar metal welded joint for connecting pipe-nozzle of nuclear pressure vessel. Different constraint equations derived from the three pairs of crack growth amount all agree with the experimental J-R curves.…”
Section: Cylinder-cylinder Intersectionsmentioning
confidence: 99%
“…The results showed that the proposed equation resulting from the parametric analysis could be employed to predict the static burst pressure of cylindrical shell intersections for a wide range of geometric ratios. Wang et al [211] obtained the equations of constraint-dependent J-R curves for the cracks of a dissimilar metal welded joint for connecting pipe-nozzle of nuclear pressure vessel. Different constraint equations derived from the three pairs of crack growth amount all agree with the experimental J-R curves.…”
Section: Cylinder-cylinder Intersectionsmentioning
confidence: 99%